2021
DOI: 10.1007/s40747-021-00321-0
|View full text |Cite
|
Sign up to set email alerts
|

A decision support system for multimodal brain tumor classification using deep learning

Abstract: Multiclass classification of brain tumors is an important area of research in the field of medical imaging. Since accuracy is crucial in the classification, a number of techniques are introduced by computer vision researchers; however, they still face the issue of low accuracy. In this article, a new automated deep learning method is proposed for the classification of multiclass brain tumors. To realize the proposed method, the Densenet201 Pre-Trained Deep Learning Model is fine-tuned and later trained using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(65 citation statements)
references
References 45 publications
(44 reference statements)
0
55
0
Order By: Relevance
“…In this survey, recent literature regarding the detection of brain tumors is reviewed, and it is indicated that there is still room for improvement. During image acquisition, noise is included in MRI, and noise removal is an intricate task [2, [262][263][264]. Accurate segmentation is a difficult task [265], as brain tumors have tentacles and diffused structures [43,193,220,266].…”
Section: Limitations Of Existing's Machine/deep Learning Methodsmentioning
confidence: 99%
“…In this survey, recent literature regarding the detection of brain tumors is reviewed, and it is indicated that there is still room for improvement. During image acquisition, noise is included in MRI, and noise removal is an intricate task [2, [262][263][264]. Accurate segmentation is a difficult task [265], as brain tumors have tentacles and diffused structures [43,193,220,266].…”
Section: Limitations Of Existing's Machine/deep Learning Methodsmentioning
confidence: 99%
“…More recently, deep learning models have been shown to significantly contribute to medical image analysis for both segmentation and classification [15,16]. In deep learning, CNNs are used for classification as they are composed of several hidden layers such as convolutional, pooling, batch normalization, ReLU, and fully connected layers [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…With this substantial number of patients in the world, different medical imaging techniques such as magnetic resonance imaging (MRI), positron emission tomography (PET), computed tomography (CT), and X-ray are used for the diagnosis [6][7][8]. Among these MRIs is the ordinary non-intrusive imaging procedure widely adopted in the clinical routine because it does not use any damaging ionizing radiations [9,10].…”
Section: Introductionmentioning
confidence: 99%